A Serial Cross-Sectional Study Investigating Unrealistic Optimism, Risk Perception and Protective Behavior during the COVID-19 Pandemic - Husna, Sabiqotul; Apriliawati, Denisa (Jurnal Psikologi, 2024)
Protective behavior is crucial and needed when crisis conditions occur, particularly in the context of the COVID-19 pandemic. This study wanted to examine whether (1) unrealistic optimism is significantly correlated to risk perception; (2) risk perception significantly affects protective behavior (3) risk perception mediates the relationship between unrealistic optimism and protective behavior and (4) whether they (unrealistic optimism, risk perception, protective behavior) are sifted from early phase to middle phase of COVID-19 Pandemic in Indonesia context. This study used a cross-sectional quantitative method, involving 549 respondents (age mean 26.02) obtained through a nonprobability (accidental) sampling technique. The study was divided into two-time windows; study I during the early period of the COVID-19 pandemic and study II when the pandemic had been running for more than 1 year. The results confirmed there was a relationship between unrealistic optimism and protective behavior, risk perception and protective behavior, but risk perception does not mediate the relationship between unrealistic optimism and protective behavior. There was a shift in the level of unrealistic optimism, risk perception, and protective behavior over time, specifically between Study I and Study II. Respondents' unrealistic optimism in Study I was at a higher level compared to Study II. The risk perception of respondents has increased along with the longer duration of the pandemic. Meanwhile, the level of protective behavior of respondents has decreased along with the longer the pandemic lasts.